1993
DOI: 10.30541/v32i4iipp.639-649
|View full text |Cite
|
Sign up to set email alerts
|

Urbanisation and Environmental Degradation in Pakistan

Abstract: The concern over the environment is not new. But the development policymakers have recently recognised that failing to take the costs of environmental damage into account will slow down the process of raising incomes and the wellbeing of the people. This recognition is in view of the fact that economic development in both industrialised and developing countries, especially during the past half century, has not been environmentally sustainable. The current debate regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Most do not control greenhouse gas emissions or other industrial wastes, which are thrown into the rivers (Luken, 2000). In this vein, Sahibzada and Qutub (1993) also confirmed that the disposal of these industrial wastes into rivers or the sea is causing high pollution stress to marine life, and also causing various life-threatening diseases in human beings. Moreover, SMEs in Pakistan are not adopting innovation related to the environment in order to reduce pollution; hence, there is an enormous need for in-depth research into the factors affecting them.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 69%
“…Most do not control greenhouse gas emissions or other industrial wastes, which are thrown into the rivers (Luken, 2000). In this vein, Sahibzada and Qutub (1993) also confirmed that the disposal of these industrial wastes into rivers or the sea is causing high pollution stress to marine life, and also causing various life-threatening diseases in human beings. Moreover, SMEs in Pakistan are not adopting innovation related to the environment in order to reduce pollution; hence, there is an enormous need for in-depth research into the factors affecting them.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 69%
“…3 A few control variables have been included in the present analysis in line with the existing literature to capture the factors (other than subsidy) that influence environmental performance of a country. The level of urbanization (urban population as a percentage of total population used as a proxy) has been included as an independent variable as uneven growth may adversely influence the environmental scenario (Jorgenson, 2004;Maiti and Agrawal, 2005;Sahibzada, 1993). A positive relationship between income and environmental sustainability is expected in line with Debashis Chakraborty and Sacchidananda Mukherjee reported empirical findings (Bruvoll and Medin, 2003;Copeland and Taylor, 2004).…”
Section: Selection Of Model and Data Sourcesmentioning
confidence: 98%
“…They found that energy consumption has positive effects on the carbon emissions. Regarding urbanization and its impact on environmental pollution in the region, Sahibzada (1993) in a study for Pakistan suggested that urbanization has three ways to degrade the environment: through industrialization, transport and energy, and poverty. The study suggested a significant role of policy makers in reducing the environmental damages that occur due to urbanization in the country.…”
Section: A Brief Review Of the Literaturementioning
confidence: 98%